Game of Thrones : Song of Ice and Fire - Book 1 - Martin, George R. R.; Dotrice, Roy 1925-; Random House Audio Publishing ([New York] : Random House Audio, 2011)
Long ago, an enigmatic event forever changed the seasons in Winterfell. Thus the land was blessed with lush summers and simultaneously cursed with harsh winters. Now, Winterfell's borders are being increasingly encroached, forcing the prominent Stark family to defend its kingdom from enemies both old and new, including the rival Lannister House and a legendary demon.
Keywords: Imaginary wars and battles -- Fiction; Imaginary places -- Fiction; Paranormal fiction; Magic -- Fiction; Kings and rulers -- Fiction; Voyages and travels -- Fiction; Betrayal -- Fiction; Dragons -- Fiction; Audiobooks; Fantasy fiction; Science fiction; Audiobooks